PENGARUH PROMOSI DAN HARGA TERHADAP MINAT BELI PELANGGAN INDIHOME DI PROPINSI DKI JAKARTA - Dr. Ismail Razak, M.Si. (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
The aim of this study was to analize the influence of promotion and price on purchase intention of customers of IndiHome in Province of DKI Jakarta. Secondary data was obtained from PT. Telekomunikasi Indonesia, Tbk, while primary data was obtained from customers of PT. Telekomunikasi Indonesia, Tbk in Province of DKI Jakarta through admission filling of questionnaire by using scale of Likert. In this study, accident sampling method was used and data analysis method was simple linear regression and multiple linear regression. The results of this study indicated that promotion and price positively and significant influenced the purchase intention of customers of IndiHome in Province of DKI Jakarta. The conclution of this study is that price was dominant than the promotion in influencing the purchase intention of customers of IndiHome in Province of DKI Jakarta.